Breaking news and Wikipedia: Writing an encyclopaedia from the journalistic point of view - Saorín, Tomás (Anuario ThinkEPI, 2017)
How current news impacts the creation of articles in the free online encyclopedia Wikipedia is studied. Unlike the traditional editorial model, Wikipedia articles on news events are produced at the same time as they happen, and, as a result, conflicts between journalism and encyclopedic criteria arise. The editorial policies and practices that the Wikipedia community of editors have been applying to the encyclopedic coverage of present facts, people, and breaking news are analyzed.
Keywords: Wikipedia; News; Encyclopaedias; Crowd journalism.